Pengaruh Pemberian Pupuk Urea dan Pupuk Organik Cair (POC) Batang Pisang terhadap Pertumbuhan dan Hasil Tanaman Pakcoy (Brassica rapa L.) - Maretta Indah Sari Simanjuntak; Cicik Suriani (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Fertilization plays an important role in increasing plant growth and yield. This study aims to analyze the effect of urea fertilizer and liquid organic fertilizer (POC) of banana stems on the growth and yield of pakcoy (Brassica rapa L.). The study was conducted in Serdang Village, Beringin District, Deli Serdang Regency, from January to August 2025 using a 4x4 factorial randomized block design (RAK) with two replications. The treatments consisted of urea doses (0, 4, 5, and 6 g/polybag) and banana stem POC concentrations (0, 60, 70, and 80 mL/L). The parameters observed included plant height, number of leaves, leaf area, total fresh weight, and root weight. Data were analyzed using two-way ANOVA and DMRT test at the 5% level. The results showed that urea fertilizer had a very significant effect on all parameters, while banana stem POC had a significant effect on most growth and yield parameters. The interaction of the two treatments had a significant effect on several parameters. The combination of 6 g urea per polybag and 80 mL/L of fertilizer-free organic fertilizer (POC) yielded the best results, while the treatment without fertilizer yielded the lowest. The combination of urea and banana stem fertilizer proved effective in increasing the growth and yield of pakcoy.